2010
DOI: 10.1111/j.1465-7295.2009.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Impact of Gender Differences in Risk Tolerance

Abstract: "This paper provides numerical estimates of the distributions of risk tolerance for men and women. A simple model of individual portfolio choice is calibrated to data on Individual Retirement Accounts from the Health and Retirement Study to obtain the estimates. Results show that women tend to be less risk-tolerant than men. The estimates are then used to measure the impact of risk tolerance on wealth accumulation. Simulations show that the difference in risk tolerance can account for around 10% of the gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 15 publications
4
49
0
5
Order By: Relevance
“…14 For a meta-analysis of studies looking at the impact of gender on negotiator competitiveness see Walters et al (1998). 15 These findings are to an extent compatible with Neelakantan (2010) who finds that about 10% of the gender gap in accumulated wealth of elderly Americans (194,000 $ for men and 95,000$ for women) is due to differences in risk tolerance, because women are more conservative investors with a significantly lower probability to invest in stocks. 16 The respective figures for 2009 are 3:49 (men) and 4:57 (women), i.e.…”
Section: Professional Sportssupporting
confidence: 81%
“…14 For a meta-analysis of studies looking at the impact of gender on negotiator competitiveness see Walters et al (1998). 15 These findings are to an extent compatible with Neelakantan (2010) who finds that about 10% of the gender gap in accumulated wealth of elderly Americans (194,000 $ for men and 95,000$ for women) is due to differences in risk tolerance, because women are more conservative investors with a significantly lower probability to invest in stocks. 16 The respective figures for 2009 are 3:49 (men) and 4:57 (women), i.e.…”
Section: Professional Sportssupporting
confidence: 81%
“…A large experimental literature that compares how men and women value risky gambles or choose between gambles, documents systematic differences in risk preferences, with women being more risk-averse than men (see Croson and Gneezy (2009) and Eckel and Grossman (2008) for an extensive review of this literature). Higher risk-aversion of women is also reflected in financial decisions (Barber and Odean, 2001;Sapienza et al, 2009;Neelakantan, 2010), decisions made by financial professionals (Dwyer et al, 2002;Beckmann and Menkhoff, 2008) and even by top executives (Bandiera et al, 2015;Belenzon et al, 2016;Faccio et al, 2016). Higher risk-aversion of women is often explained by their relatively lower overconfidence (Lundeberg et al, 1994;Barber and Odean, 2001).…”
Section: H1mentioning
confidence: 99%
“…To date, researchers report that women are, in general, more risk averse (Bajtelsmit and Bernasek, 1996; Bajtelsmit and VanderHei, 1997; Bajtelsmit et al, 1999; Grable, 2000; Hallahan et al, 2004; Faff et al, 2008; Neelakantan, 2010); this has also been confirmed in a meta-analysis of over 150 studies conducted by Byrnes et al (1999). The results pointed to a greater overall propensity of men than women to take various types of risk (e.g., the use of drugs, smoking cigarettes, drinking alcohol, risky sexual behaviors, the way of driving the car and many others).…”
Section: Introductionmentioning
confidence: 99%